Estudio de la prevalencia de Staphylococcus Aureus en fosas nasales de los expedientes de comidas preparadas de Mercado Municipal Las Mercedes de la ciudad El Guabo - Ramón Rivas, Fabricio K. (2011)
Staphylococcus aureus has been recognized as an important pathogen in human disease remains a frequent cause of many infections: mild, such as pyuderma, and severe, such as osteomyelitis, sepsis, endocarditis, among others.